Refinement of the grain structure of selective laser melted Ti-6Al-4V via induction heat treatment - Zou, Zhiyi (2020)
Selective laser melting (SLM) has been shown to be an attractive manufacturing route for the production of α/β titanium alloys, and in particular Ti-6Al-4V. Post-process heat treatments are widely used to tune the microstructure and improve the mechanical properties of the as-built parts. However, conventional heat treatments cannot transform the coarse elongated prior-β structure in a satisfying way, which limits the use of Ti-6Al-4V produced by SLM. The principal aim of the present study is to investigate how the initial microstructure formed in SLM can be exploited to achieve β-grain refinement via induction heat treatment. The microstructure and tensile properties following such heat treatments are discussed. As well as the microstructure evolution and recrystallisation phenomena responsible for the refinement.